CTX-M-producing Escherichia coli ST602 carrying a wide resistome in South American wild birds: Another pandemic clone of One Health concern - Dalazen, Gislaine; Fuentes-Castillo, Danny; Pedroso, Luiz G. [UNESP]; Fontana, Herrison; Sano, Elder; Cardoso, Brenda; Esposito, Fernanda; Moura, Quezia; Matinata, Bianca S.; Silveira, Luiz F.; Mohsin, Mashkoor; Matushima, Eliana R.; et al. (Elsevier, 2023)
Wild birds have emerged as novel reservoirs and potential spreaders of antibiotic-resistant priority pathogens, being proposed as sentinels of anthropogenic activities related to the use of antimicrobial compounds. The aim of this study was to investigate the occurrence and genomic features of extended-spectrum β-lactamase (ESBL)-producing bacteria in wild birds in South America. In this regard, we have identified two ESBL (CTX-M-55 and CTX-M-65)-positive Escherichia coli (UNB7 and GP188 strains) colonizing Creamy-bellied Thrush (Turdus amaurochalinus) and Variable Hawk (Geranoaetus polyosoma) inhabiting synanthropic and wildlife environments from Brazil and Chile, respectively. Whole-genome sequence (WGS) analysis revealed that E. coli UNB7 and GP188 belonged to the globally disseminated clone ST602, carrying a wide resistome against antibiotics (β-lactams), heavy metals (arsenic, copper, mercury), disinfectants (quaternary ammonium compounds), and pesticides (glyphosate). Additionally, E. coli UNB7 and GP188 strains harbored virulence genes encoding hemolysin E, type II and III secretion systems, increased serum survival, adhesins and siderophores. SNP-based phylogenomic analysis, using an international genome database, revealed genomic relatedness (19–363 SNP differences) of GP188 with livestock and poultry strains, and genomic relatedness (61–318 differences) of UNB7 with environmental, human and livestock strains (Table S1), whereas phylogeographical analysis confirmed successful expansion of ST602 as a global clone of One Health concern. In summary, our results support that ESBL-producing E. coli ST602 harboring a wide resistome and virulome have begun colonizing wild birds in South America, highlighting a potential new reservoir of critical priority pathogens.
Keywords: Antimicrobial resistance; ESBL; Genomic surveillance; High-risk clone; WHO priority pathogens; Wildlife